Vouching for childcare assistance with two quasi-experimental studies. Issue 8 (4th November 2014) - L. Gullekson, Nicole; Griffeth, Rodger; B. Vancouver, Jeffrey; T. Kovner, Christine; Cohen, Debra
Abstract : Purpose: – Human resource management (HRM) practices are implemented to improve outcomes, such as reducing turnover, absenteeism, and improving performance. Using social exchange theory (SET), the purpose of this paper is to examine one HRM practice that has received less attention by researchers: employer-sponsored childcare assistance programs. Design/methodology/approach: – Study 1 – a field study compared three groups of hospital employees' ( n =148) attitudes and behaviors using MANCOVA/ANOVA over two time periods. Study 2 – using a field study, on-site and voucher childcare assistance programs were evaluated in terms of the cost to the organization and the relationship to attitudinal variables. Findings: – Study 1 – results indicated that employee performance was higher and absenteeism lower for employees using the on-site childcare center than employees using an off-site center or with no children. Although the attitudinal results did not align with hypotheses, they were not inconsistent with SET. Study 2 – results indicate that childcare assistance programs may be a beneficial HRM practice for organizations to implement. Research limitations/implications: – One limitation of Study 1 is the small sample size. Future research should continue to examine how employee benefits like childcare programs affect employees, as well as examine how such benefits differentially employees who value and do not value the benefits. In Study 2, although the authors randomly selected the sample of on-site and voucher programs, the health care facilities self-selected themselves to participate in the program and selected the type of childcare program, a potential source of bias. Future research should examine childcare assistance programs and their impact on work-family balance and strain-based conflict in a wider variety of samples. Practical implications: – Implications for research and practice: Both studies offer researchers a "next step" in the evaluation of childcare assistance research. Additionally, these studies are of practical value to administrators/researchers in organizations who may be considering vouchers or on-site programs as they relate such programs to organizational outcomes. Originality/value: – The first study is one of the few studies on this topic to use a field design with two time points and with multiple behaviors and attitudes. The second study provides a descriptive comparison of two types of childcare assistance programs, a comparison made by few studies to date.